From Digital Divides to the First Mile: Indigenous Peoples and the Network Society in Canada - McMahon, Rob (USC Annenberg School for Communication & Journalism, 2014)
Indigenous peoples interact with the emergent network society in diverse ways that reflect the colonialism/self-determination dialectic. One area where this process unfolds is in the bridging of digital divides. I use the concept of the First Mile to show how First Nations and Inuit peoples in Canada’s geographic periphery are asserting their self-determination in the sphere of digital ICTs. While most digital divide literature presumes that a connection to the network society is inherently beneficial, when framed in the context of historic and ongoing processes of colonialism, integration alone is not adequate. An example of a not-for-profit satellite network cooperative demonstrates how three Indigenous organizations shaped the problem of the digital divide into an opportunity to establish a platform for digital self-determination.